Estimates of true amino acid digestibilities in feed ingredients using precision-fed, cecectomized roosters - Bellaver, Claudio; Parsons, Carl; A. Easter, Robert (Pesquisa Agropecuaria Brasileira, 1998)
Twenty seven cecectomized mature Single Comb White Leghorn cockerels were used to estimate true amino acid digestibilities (TAAD) coefficients for eight feedstuffs for cecectomized roosters. The objective of this paper was to evaluate alternative feed ingredients TAAD coefficients using a standard precision fed (crop-intubation) methodology. The ingredients tested were corn, wheat bran (WB), two sources of soybean meal (SBM 1 and SBM 2), cottonseed meal (CSM), poultry by-product (PBP), and two samples of meat and bone meal (MBM 1 and MBM 2). A group of three roosters was fasted 24 hours prior to each assay to allow measurement of endogenous amino acid production. True lysine digestibility (TLD) in CSM (71.8%) was significantly lower (P < 0.01) than in all the other feed sources. No differences (P > 0.01) were found for TLD among the other ingredients. Means and standard error of means for TAAD were: corn 103.03±4.30, WB 90.35±2.26, SBM 1 93.13±1.55, SBM 2 92.99±2.39, CSM 81.16±4.67, PBP 86.23±2.14, MBM 1 86.20±2.49, MBM 2 85.98±2.26. In general the averages of the coefficients for TAAD of the ingredients used are in the range of the values reported in the literature and can be used to formulate diets based on amino acid digestibility.
Keywords: poultry; feedstuffs; forced feeding; metabolism; digestion